2018
DOI: 10.2147/ott.s165436
|View full text |Cite
|
Sign up to set email alerts
|

Triclosan treatment decreased the antitumor effect of sorafenib on hepatocellular carcinoma cells

Abstract: BackgroundTriclosan is a widely applied antimicrobial agent which affects the endocrine system and homeostasis; it may also promote the cirrhosis and hepatocellular carcinoma (HCC) growth in a mice model. The exact roles of triclosan in regulating human hepatocellular carcinoma development and treatment remain unknown.MethodsMHCC97-H, a highly aggressive HCC cell line, was treated with indicated concentration of triclosan or sorafenib. The expression of drug-resistance genes was examined by qPCR. The clearance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Hepatic cell lines: L-02 (a non-tumor hepatic cell line), MHCC97-H, or LM-3 (two highly metastatic cell lines of HCC), HepG2, Hu7, BEL-7402, or SMMC-7721 (cell lines of HCC), and MHCC97-L (a lowly metastatic cell line of HCC) were purchased from the Type Culture Collection of the Chinese Academy of Sciences (Shanghai, China) or the National Infrastructure of Cell Line (Institute of Basic Medicine, Chinese Academy of Medical Science, Beijing, China); these are the two culture collection centers of the Chinese government. Five patient-derived HCC (PDC) cell lines were provided by Dr Fan Feng at the Research Center for Clinical and Translational Medicine at the 302nd Hospital of Chinese People's Liberation Army (Beijing, China) 33 . The cell lines were maintained in our lab under conditions, which were previously described 34,35 .…”
Section: Patients and Agentsmentioning
confidence: 99%
“…Hepatic cell lines: L-02 (a non-tumor hepatic cell line), MHCC97-H, or LM-3 (two highly metastatic cell lines of HCC), HepG2, Hu7, BEL-7402, or SMMC-7721 (cell lines of HCC), and MHCC97-L (a lowly metastatic cell line of HCC) were purchased from the Type Culture Collection of the Chinese Academy of Sciences (Shanghai, China) or the National Infrastructure of Cell Line (Institute of Basic Medicine, Chinese Academy of Medical Science, Beijing, China); these are the two culture collection centers of the Chinese government. Five patient-derived HCC (PDC) cell lines were provided by Dr Fan Feng at the Research Center for Clinical and Translational Medicine at the 302nd Hospital of Chinese People's Liberation Army (Beijing, China) 33 . The cell lines were maintained in our lab under conditions, which were previously described 34,35 .…”
Section: Patients and Agentsmentioning
confidence: 99%
“…For cultured MHCC97-H cells, cells were harvested after sorafenib treatment at the indicated time points and then harvested for liquid chromatograph-mass spectrometer/mass spectrometer (LC-MS/MS) examination. 23 For the subcutaneous tumor model, MHCC97-H or HepG2 cells which were infected with miR-140-3p or PXR, were seeded into nude mice to form subcutaneous tumors. Sor-Sol was injected into subcutaneous tumors (20 ”L per tumor) in the subcutaneous tumors of the nude mice formed by HCC cells.…”
Section: Methodsmentioning
confidence: 99%
“…The sequences and effects of PXR siRNA and ETS-1 siRNA are described in our previous work. 38,45 The pharmacokinetic experiments were performed according to the methods provided by Shao et al 46 and Wu et al 47 For cell-based experiments, HCC cells were treated with 1 ÎŒmol/L sorafenib for 12 hours. Then the cells were harvested at indicated time points.…”
Section: Pharmacokinetic Experimentsmentioning
confidence: 99%
“…Moreover, previous work from our lab had revealed that, HGF/c-MET signaling pathway promoted sorafenib resistance by enhancing PXR downstream drug resistance-related genes' expression via interaction between PXR and ETS-1. 45 To further examine the effect of ARQ-197, luciferase experiments were performed. We transfected ETS-1 responsible gene reporter plasmid EBS-Luc or PXR responsible gene reporter plasmids DR3-Luc or ER6-Luc, respectively, and then administered ARQ-197.…”
Section: Arq-197 Inhibits the Transcription Factor Activities Of Ets-mentioning
confidence: 99%